Zahteve gimnazijskih učiteljev pri ocenjevanju znanja - Ivanuš-Grmek, Milena (Šolsko polje, 2008)
In the paper the results of empirical research are presented. They describe the implementation of the gymnasium programme in 29 out of 56 Slovenian general gymnasiums. The research was done within the evaluation study Evaluation study of the gymnasium education regarding the comprehension of the curriculum, the interaction of knowledge and the representation of objectives, carried out at the Educational Research Institute, Ljubljana. There were 420 gymnasium teachers and 3104 students participating in the study. The principal research question was how the instruction is being carried out during different phases: preparing for the lessons, discussing the new contents and knowledge assessment. This paper focuses on the phase of knowledge assessment and the content requirements of teachers when assessing the knowledge. Regarding the content requirements of teachers when assessing the knowledge the results have demonstrated differences in estimating individual requirements of a teachers between teachers of different subject fields, teachers who teach the first years' students and those who teach last years' students and differences between teachers' and students' estimation of certain content requirements when assessing the knowledge.
Keywords: gimnazije; ocenjevanje; preverjanje znanja; učni načrti